ROMANIAN CREATIVITY. CREATIVE THINKING IN ROMANIA - LINDA. D. TAYLOR; STEVEN HARLOW; RAMONA MUNTEANU (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. This is an exploratory study of creative thinking in Romania. The Torrance Test of Creative Thinking (TTCT) was administered to 46 Romanians (19 high school students, 18 university students, and 9 adults). A profile on the TTCT of the Romanian sample was identified for the global Standard Composite Score and Creativity Index, with the five normative scales (Fluency, Originality, Abstractness of Titles, Elaboration and Resistance to Premature Closure), as well as the thirteen criterion-referenced Creativity Strengths. A significant difference was discovered between the Romanian profile of creative thinking and the American profile of creative thinking. Implications are examined.